Sleep disturbances and psychological well-being among military medical doctors of the Swiss Armed Forces: study protocol, rationale and development of a cross-sectional and longitudinal interventional study - Sadeghi-Bahmani, Dena; Rigotti, Viola; Stanga, Zeno; Lang, Undine E.; Blais, Rebecca K.; Kelley, Michelle L.; Brand, Serge (Frontiers in Public Health, 2024)
Background: Despite their responsibility and workload, no research has examined sleep disturbances and psychological well-being among the medical doctors (MDs) of the Swiss Armed Forces (SAF). The aims of the proposed study are (1) to conduct a cross-sectional study (labelled ‘Survey-Study 1’) of sleep disturbances and psychological well-being among military MDs; (2) to identify MDs who report sleep disturbances, along with low psychological well-being both in the private/professional and military context, and (3) to offer those MDs with sleep disturbances an evidence-based and standardized online interventional group program of cognitive behavioral therapy for insomnia (eCBTi) over a time lapse of six weeks (labelled ‘Intervention-Study 2’). Method: All MDs serving in the SAF (N = 480) will be contacted via the SAF-secured communication system to participate in a cross-sectional survey of sleep disturbances and psychological well-being (‘Survey-Study 1’). Baseline data will be screened to identify those MDs who report sleep disturbances; they will be re-contacted and randomly assigned either to the eCBTi or the active control condition (ACC) (‘Intervention-Study 2’). Individuals in the intervention condition will participate in an online standardized and evidence-based group intervention program of cognitive behavioral therapy for insomnia (eCBTi; once the week for six consecutive weeks; 60-70min duration/session). Participants in the ACC will participate in an online group counseling (once the week for six consecutive weeks; 60-70min duration/session), though, the ACC is not intended as a bona fide psychotherapeutic intervention. At the beginning of the intervention (baseline), at week 3, and at week 6 (post-intervention) participants complete a series of self-rating questionnaires as for the Survey-Study 1, though with additional questionnaires covering sleep-related cognitions, experiential avoidance, and dimensions of self-awareness. Conclusions: The study offers the opportunity to understand the prevalence of sleep disturbances, including factors of psychological well-being among MDs of the SAF. Further, based on the results of the Intervention-Study 2, and if supported, eCBTi may be a promising method to address sleep disturbances and psychological well-being among the specific context of military doctors in the SAF.